Improving Student Motivation and Learning Outcomes Through the Student Team Achievement Divisions Model - Nurjani Nurjani (Pinisi Journal of Education and Management, 2023)
Biology is a science that deals with natural phenomena and objects that are systematically arranged regularly, and generally accepted in the form of a collection of observations and experiments. Biology has a very important role in providing an understanding of the characteristics and phenomena of nature, as well as of living things and life processes. Therefore, the purpose of this study is to increase student motivation and learning outcomes through the Student Team Achievement Divisions (STAD) model in Biology class XI IPA 3 SMAN 7 Sigi. 33 students of class XI IPA 3 consisting of 9 males and 24 females using data collection techniques, namely qualitative data and quantitative data. Data collection techniques for each type of data are 1) Qualitative data is collected by using observation sheets, namely making a series of direct observations of researchers during the learning process; and 2) Quantitative data is collected by giving tests at the end of each cycle. The data analysis technique used is data reduction, data presentation, and conclusion. The data obtained were analyzed using the percentage of individual absorption and classical completeness techniques obtained by students. The results of this study indicate that 1) The application of the Student Team Achievement Divisions (STAD) model can increase student learning motivation in Biology class XI IPA 3 SMAN 7 Sigi even semester of the 2022/2023 academic year; 2) The application of the Student Team Achievement Divisions (STAD) model can improve student learning outcomes in Biology class XI IPA 3 SMAN 7 Sigi even semester of the 2022/2023 academic year; 3) The application of the Student Team Achievement Divisions (STAD) model can increase student motivation and learning outcomes in Biology class XI IPA 3 SMAN 7 Sigi even semester of the 2022/2023 academic year